Forming new words: Compounds in Devayan - Zulfadli Abdul Aziz; Bukhari Daud; Muhammad Wiwin (Universitas Syiah Kuala, 2019)
As a part of word formation in the morphological process, compounding generally covers the types of words to be combined. This present study seeks the morphological process in forming words through compounding in the Devayan language spoken in Simeulue, Aceh, Indonesia. This study is also to analyze the meaning that occurs from the result of the compounding process. In collecting the data, this research uses the elicitation technique which is constructed by Bowern (2015). The informants of this research are the native Devayan who live in La’ayon, Angkeo, Naibos and Maudil, Teupah Barat sub-district, Simeulue. The research finds that the compounding process in Devayan consists of compounding of two nouns, compounding of noun and verb, compounding of noun and adjective, compounding of verb and adjective, compounding of verb and noun, and compounding of adjective and noun and compounding of two verbs. The result of the process produces some meanings, namely about (1) the product, (2) specific use, (3) time, and (4) condition. This study indicates that Devayan uses various compound words with different morphological processes. It is hoped that this study is beneficial for its natives as documentation and non-native as a reference to compounding formation in the language.